Regenerative potential of secretome derived from human exfoliated deciduous teeth stem cell on osteoarthritic chondrocytes - Muhammad, Suleiman Alhaji (2019)
Osteoarthritis (OA) is a degenerative joint disease that remains a major clinical challenge due to limited intrinsic healing capacity of articular cartilage. The current therapies are only effective in symptoms or pain relief and offer short-term benefits. Recent studies utilising mesenchymal stem cells (MSCs) for the treatment of osteoarthritis have shown promising results. However, emerging evidence suggests that the therapeutic benefits of MSCs are mediated through paracrine mechanism due to multiple secreted factors that modulate the defective tissue to evoke reparative and regenerative processes. Thus, the objective of this thesis was to investigate the regenerative potential of the secretome of stem cells from human exfoliated deciduous teeth (SHED) for the treatment of osteoarthritis. To realise this objective, viable chondrocytes were isolated from cartilage using enzymatic digestion and characterised for the expression of the cartilage-specific phenotype. Secretome prepared from SHED was used to treat interleukin-1β (IL-1β)-stimulated chondrocytes as the OA in vitro model. The level of interleukin-10 (IL-10), transforming growth factor-β1 (TGF-β1) and interleukin-6 (IL-6) were assessed in stimulated chondrocytes incubated with secretome. Furthermore, the expression of aggrecan, collagen type 2, a disintegrin metalloproteinase with thrombospondin motifs 4 (ADAMTS4), matrix metalloproteinase-13 (MMP-13) and nuclear factor-kB (NF-kB) were also evaluated. Results showed that the number of viable chondrocytes yield per gram of cartilage was significantly higher in collagenase type II as compared with trypsin. Aggrecan and collagen type 2 were highly expressed in the isolated chondrocytes, indicating that the cells retained cartilage-specific phenotype. SHED highly expressed MSC markers (CD44, CD73, CD90, and CD105), but were negative for haematopoietic markers. SHED also showed protein expression of NANOG, OCT4 and SOX2 with differential subcellular localisation. Interestingly, the results also revealed that secretome significantly decreased (p<0.05) IL-6 level in osteoarthritic chondrocytes compared to serum-free medium (SFM) control group. The level of TGF-β1 was higher in cells treated with secretome compared to stimulated cells incubated in SFM. Meanwhile, the level of IL-10 was significantly lowered in stimulated cells treated with secretome compared to stimulated cells incubated in SFM. However, IL-10 level in IL-1β-stimulated cells treated with secretome was similar to non-stimulated cells. Furthermore, the expression of MMP-13 and NF-kB was significantly downregulated in stimulated cells incubated with secretome when compared with stimulated cells incubated in SFM. Similarly, a decrease mRNA expression of ADAMTS4 was observed in osteoarthritic chondrocytes incubated with secretome compared to SFM. Secretome also increased the expression of aggrecan and collagen type 2 when compared with stimulated cells incubated in SFM. Thus, secretome may act to regenerate extracellular matrix proteins and modulate proteinases and inflammatory activities through inhibition of NF-kB. The results highlighted the potential use of secretome for cartilage repair and regeneration.